Mathematics in the Elementary School - Ediger, Marlow ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This paper discusses the various aspects of mathematics teaching and learning at the elementary school level. The National Council of Teachers of Mathematics (NCTM) standards are reviewed by giving examples and a list of principles of learning in mathematics is offered. Principles include the following: 1) the need for pupils to perceive learning activities that are meaningful; 2) mathematics teachers needs to pay attention to the rate of presentation at which pupils may understand and attach meaning to what is taught; 3) the need for pupils to experience a variety of learning opportunities in the mathematics curriculum; 4) the need to experience individual and collaborative endeavors; 5) the need for teachers to minimize lecturing as a method of instruction; 6) the need for a work environment that is conducive to achieving in mathematics; 7) "mathematics for all" is important to stress; 8) achievement in three main categories of objectives in mathematics; 9) emphasis on a hands-on approach to learning; and 10) application of that which has been learned. (ASK)
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Education; Elementary School Mathematics; Learning Activities; Learning Processes; Mathematics Curriculum; Mathematics Education; Standards; Teaching Methods; Guides, Classroom -- Teacher